The Influence To Service Quality, Facilities, and Ticket Price on Passenger Satisfaction at PT. Pelni (Persero) Baubau Branch - Hasan, Muslihati; Ningrat, Andi; Usman, Arif Fuddin; Fitriah, Rifkah; Rachmianty, andi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2024)
Sea transportation is the most important means of inter-island connectivity in Indonesia. Companies must try to make customers feel satisfied by providing better offers and services, companies must be able to maintain their market position in the midst of increasing competition. The purpose of this study was to evaluate the variables of service quality, facilities and ticket prices partially on passenger satisfaction at PT. Pelni (Persero) Baubau Branch. Evaluating the quality of services, facilities and ticket prices simultaneously on passenger satisfaction and evaluate which of the three parameters used has the most influence on passenger satisfaction. The data used in this study are primary data obtained by distributing questionnaires to the passengers of PT. Pelni (Persero) Baubau Branch has 50 employees using multiple linear regression analysis techniques. The results showed that Service Quality (X1) had a significant level of 0.013 <0.05. This means that service quality has a positive and significant effect on passenger satisfaction. Facility (X2) has a significant level of 0.012 <0.05. This means that facilities have a positive and significant effect on passenger satisfaction. Ticket prices (x3) have a significant level of 0.019 <0.05. This means that ticket prices have a positive and significant effect on passenger satisfaction.